A 15-year comprehensive literature review of 99 primary ovarian carcinoid tumors - Tiberiu-Augustin Georgescu; Roxana Elena Bohiltea; Valentin Varlas; Octavian Munteanu; Florentina Furtunescu; Antonia-Carmen Lisievici; Corina Grigoriu (IMR Press, 2022)
Objective: Primary ovarian carcinoids are neuroendocrine tumors, representing up to 1% of all ovarian tumors. In this paper, the authors aimed at analyzing the clinical and pathological aspects of all recently published ovarian carcinoid, providing new correlations regarding them. Mechanism: The authors have reviewed all cases of primary ovarian carcinoid reported in international journals since 2005 to date. A total of 99 cases published in 68 articles have been found and analyzed. Findings in brief: Our results up to 29.31% of patients presented with carcinoid heart disease, and 17.24% had an abdominal mass, which caused them to present to the physician. Patients presenting with metastases had more frequently the insular subtype (33.33%) and had similar median age as those without metastases. A teratoma component was noticed in 58.9% of cases and was also associated with the insular pattern of carcinoid. To our best knowledge, this paper includes the largest review of primary ovarian carcinoid to date. Conclusions: The incidence of carcinoid heart disease might have been underestimated up to this moment, thus, requiring further imagistic investigations of patients presenting with these symptoms. Additionally, the insular variant was most frequently associated with the presence of both teratoma (52.94%) and metastases (33.33%), although previous reports have noticed a higher incidence of teratoma in the mucinous variant. In our opinion, these apparently divergent results warrant further studies of this rare subtype of ovarian tumor.